Escola e violência: representações sociais de um grupo de educadores de escolas públicas estaduais de Cuiabá- MT - Saul, Léa Lima (2010)
The violence is one of the problems that afflict the Brazilian contemporary society, provoking fear and unreliability. In the school, the violence is a question of concern for the teachers, the students and for the pedagogical professionals especially at the schools from the net of public education. The objective of this research that originated this thesis was to identify and analyze the social representations of violence in the school constructed by a teachers group from the state public schools in Cuiabá in the state of Mato Grosso. The Theory of the Social Representations by Serge Moscovici and his collaborators served as guiding center line to reach the aim. The data gathered for the social representations study initially counted on observations sessions in the studied schools. Following semi-structuralized interviews were carried out, in private sessions, with thirty one teachers, seven pedagogical coordinators and twelve directors, distributed in sixteen schools in the urban perimeter of the capital city. The discursive material originated from the interviews was processed by software ALCESTE. The analyses revealed that the subjects construct their social representations about violence in the school by means of the verbal communication, in their daily informal conversations with the colleagues, sharing the experiences and also by the communication means, focused on the television and newspapers. The causes of the violence in the school which were in consensus at the representations for the majority of the subjects are objectified on what they consider as non structured family of the students. They are anchored in the lack of respect of the youths with their colleagues and other members of the school. The subjects objectified the violence in an illness spreading as a big tree extending its brushes and roots. For most of the teachers the presence of a psychologist in the school is the objectified as support, assistance, protection and efficient orientation to deal with the violence, for the students, teachers and parents. Concerning to the consequences of the violence in the school, the subjects place their representations in two distinct forms: those who see the impact in the teaching work, causing lack of motivation and those who identify the effect in the students, promoting deficient learning and the inadequacies at the society